Effects of various surface treatments on the storage life of guava (Psidium guajava L) at 10°C - Mohamed, Suhaila; Kyi, Khin Ma Ma; Yusof, Salmah (Wiley, 1994)
The use or various surface treatments to prolong storage life of guavas at 10°C was examined. LDPE shrinkwrap was most effective in reducing weight loss and maintaining the firmness of guava (most likely indicating its effectiveness in alleviating water stress), followed by clingwrap packaging and 200 g litre−1 palm oil emulsion coating. The skin colour of guava was most effectively preserved by LDPE packaging, sucrose‐ester and 200 g litre−1 palm oil emulsion dips. Paraffin treatment caused the skin to turn brown after 2 weeks storage. The ascorbic acid content was highest in control followed by clingwrapped guava. Clingwrapped guava also received the highest organoleptic scores followed by shrinkwrapping and 200 g litre−1 palm oil treated guava.